2011
DOI: 10.1200/jco.2011.29.15_suppl.2026
|View full text |Cite
|
Sign up to set email alerts
|

Impact of meningeal dissemination (MD) on outcome in primary CNS lymphoma in the G-PCNSL-SG1 trial

Abstract: Background: The prognostic impact of MD in PCNSL is still debated. Within the framework of a multicenter randomized trial (G-PCNSL-SG1) we evaluated patients for outcome according to the presence of MD. Methods: Immunocompetent adult patients were initially treated with up to six cycles of high-dose methotrexate (HD-MTX; 4g/m 2) based chemotherapy without intrathecal therapy. Those randomized to radiotherapy subsequently received whole-brain radiotherapy (WBRT) with 45 Gy, in 1.5 Gy fractions; those randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Three articles were derived from the large (n = 411) German primary CNS lymphoma randomized trial of high-dose methotrexate (HD-MTX) with or without ifosfamide followed in patients with a complete response to observation or whole brain RT [14][15][16][17]. The trial demonstrated no advantage to upfront RT and was further analyzed with respect to prognostic variables affecting survival, as well as chemotherapy-related toxicity [18].…”
Section: Primary Cns Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…Three articles were derived from the large (n = 411) German primary CNS lymphoma randomized trial of high-dose methotrexate (HD-MTX) with or without ifosfamide followed in patients with a complete response to observation or whole brain RT [14][15][16][17]. The trial demonstrated no advantage to upfront RT and was further analyzed with respect to prognostic variables affecting survival, as well as chemotherapy-related toxicity [18].…”
Section: Primary Cns Lymphomamentioning
confidence: 99%
“…Similarly, chemotherapy-related toxicity was a function of low performance (<70), advanced age (>60 years), receipt of HD-MTX and ifosfamide (compared with HD-MTX only), elevated serum LDH and pre-existing pulmonary or cardiovascular disease [16]. The German primary CNS lymphoma study also analyzed whether evidence of CSF dissemination at diagnosis affected outcome as determined by CSF cytology, polymerase chain reaction (PCR) gene rearrangement or MRI [17]. Despite no intra-CSF chemotherapy being administered in this study, outcome in the 19% of patients with CSF dissemination was similar to that of patients without evidence of CSF dissemination.…”
Section: Primary Cns Lymphomamentioning
confidence: 99%